Metodologia participativa na avaliação da qualidade do solo e as inter-relações de atributos em agroecossistemas - Queiroz, Gabriela Carvalho Maia de (Universidade Federal Rural do Semi-Árido, 2020)
Knowing the quality of a soil is an arduous task, given the dynamics of the interrelations it presents with the environment. The union between popular and scientific knowledge is essential for planning of practices that will guarantee its conservation, since information that complement each other in understanding the area. The aim of the work was to compare the results obtained by the participative and analytical methodologies in the characterization of soil quality, using multivariate analysis to differentiate the environments. The research was carried out in Piracicaba community, located at the municipality of Upanema, Rio Grande do Norte. Three areas were evaluated (Mata Preservada, Horta and Pastejo de Ovinos). In participative methodology, students and teachers answered questionnaires to evaluate the indicators. From the answers obtained, the average of the marks awarded was considered for making radar-type graphics. The disturbed and undisturbed samples (volumetric ring and blocks) were collected and taken to the laboratory for analysis in triplicate and quadruplicate (aggregates). Of these, the physical, structural and chemical attributes were quantified, to be submitted to multivariate statistical techniques, through the correlation matrix, cluster analysis and factor analysis with extraction of the factors in main components. Factor analysis showed sensitivity in discriminating environments for the attributes clay, total organic carbon (TOC), base saturation (V) and percentage of exchangeable sodium (ESP) in Factor 1, and sand, silt, clay activity, pH(water), sum of bases (SB) and phosphorus (P) for Factor 2. The cluster analysis separated the environments into three groups, the physical-structural ones showed greater dissimilarity, showing the relationship between soil classes and uses (Group I), followed by aeration porosity (Paer.) and the chemicals total organic carbon (COT), pH(water) and sum of bases (SB) (Group II) and the physical total porosity (PT), chemicals clay activity (Activ Clay) and base saturation (V) and sand, silt and clay particle sizes (Group III - Cambisol). The clay fraction showed an interrelation with chemical attributes (Factor 1) in the distinction of soil classes and uses. All environments studied were eutrophic (V≥50%), due to the source material (Calcário Jandaíra). The Preserved Forest environment showed no physical or chemical restrictions. The TOC was sensitive in discrimination of Horta and Pastejo de Ovinos agroecosystems. All environments showed good chemical characteristics. The Mata Preservada ecosystem showed physical, structural and chemical quality
Keywords: Agricultores(as) familiares; Classes de solos; Avaliação quali-quantitativa; Semiárido Potiguar; Multivariada; Family farmers; Soil classes; Qualitative and quantitative assessment; Potiguar semiarid; Multivariate; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA